Outsourcing in Healthcare Through Process Modularization A Lean Perspective - Guimarães, M.; Crespo de Carvalho, J. (International Journal of Engineering Business Management, 2012)
Looking for efficiency, quality and profitability gains, healthcare organizations are adopting outsourcing solutions in the attempt of "doing more with less". Seeking for cost reduction, risk mitigation, adapting to quick changes without compromising internal resources, these organizations also take big risks in control and flexibility variables. In order to understand how healthcare organizations find the best value equation combining internal and external resources in a modular service conception, a case study on a start-up Long-term Care unit with innovative format, great levels of customization and following an outsourcing strategy, was carried out. The main conclusion, among others, is that in ambitious start-ups, having speed of entrance as the conditioning factor, a process orientation and management approach may offer a clear view of the gains related with trade-off decisions regarding time and cost (agility) and cost and quality (Leanness) ie, decisions under the "leagile" paradigm. This study contributes for a wider understanding of the "leagile" concept associated to an outsourcing operational strategy. Additionally, it also provides new insights to the concept of modularity in services settings in a complex service as healthcare.